Penerapan Pendekatan Deep Learning untuk Meningkatkan Keterampilan Menulis Teks Eksplanasi pada Murid Kelas VI SDN Subo 02 Jember - Anjani, Nadya Putri (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study is motivated by the low ability of sixth-grade students at SDN Subo 02 Jember in writing explanatory texts. Based on interviews and assessment results, only 5 out of 16 students achieved the learning objectives achievement criteria, indicating difficulties in developing ideas, organizing text structures, and using appropriate vocabulary. This condition is influenced by low reading skills and the lack of learning strategies that support deep understanding. This study aims to describe the implementation of the deep learning approach and improve students’ explanatory text writing skills. The method used was Classroom Action Research conducted in three cycles, consisting of planning, action, observation, and reflection stages. Data collection techniques included observation, interviews, tmuridests, and documentation. The results showed an increase in learning mastery from 31.25% in the pre-cycle to 37.5% in cycle I, 50% in cycle II, and 75% in cycle III, indicating that the deep learning approach effectively improves students’ writing skills overall.
:: Finalisasi file repositori 16 Juli 2026_Kurnadi
Keywords: Penerapan; Deep Learning; Teks Eksplanasi; Keterampilan Menulis